Reference levels of mean and peak anaerobic power for male and female long-track speed skaters - Sitkowski, Dariusz; Starczewski, Michał; Klusiewicz, Andrzej (Biology of Sport, 2025)
The ability to generate and maintain high power is a prerequisite for success in many sports, including long-track speed skating. A common method of determining this ability is the Wingate test, but surprisingly, normative data necessary to objectively assessthe performance ofspeed skatersislacking. Therefore, the present study aimed to develop reference levels for peak power (PP) and mean power (MP) on a Wingatetype test for speed skaters using a Monark 874E ergometer with a load equivalent to 7.5% of body mass. Over 15 years, 635 test results were collected from 120 junior and senior athletes (all national representatives); 380 from men and 255 from women. We found that in men and women, personal best in relative PP and MP (W/kg body mass) correlated significantly (all p < 0.001) with altitude-adjusted times over distances of 500 ( r = -0.75 to -0.82) and 1000 m ( r = -0.67 to -0.71), thus confirming the validity of this test for assessing the on-ice sprinting ability of speed skaters. Moreover, the two-way ANOVA models revealed significant effects of gender ( p < 0.001) and age ( p < 0.001) on relative MP and PP (W/kg) values, but the interaction effect was not significant ( p > 0.05). The 7-stage classification system constructed on the basis of the obtained results enables the assessment of relative MP and PP in Wingate tests, taking into account the age category and gender of the athletes. This system can be used by sports researchers and coaches to assess the sprinting ability of speed skaters from novice to world-class levels.